2013
DOI: 10.1097/01.aids.0000432444.30308.2d
|View full text |Cite
|
Sign up to set email alerts
|

The long-term efficacy of medical male circumcision against HIV acquisition

Abstract: The efficacy of MMC was sustained at 58% at 72 months, similar to overall findings of the three trials under conditions of randomization. These findings provide an estimate of the long-term efficacy of circumcision against HIV acquisition. Our results support programmatic scale-up recommendations that are based on assumptions of sustained efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 20 publications
2
51
0
Order By: Relevance
“…We assumed that MMC reduced the risk of HIV acquisition in men by 60% [18] and that suppressive ART reduced the transmission risk by 73%-99% [3] and prolonged survival among HIV-infected persons [4]. PrEP scenarios assumed the scale-up of PrEP in combination with ART and MMC.…”
Section: Interventionsmentioning
confidence: 99%
“…We assumed that MMC reduced the risk of HIV acquisition in men by 60% [18] and that suppressive ART reduced the transmission risk by 73%-99% [3] and prolonged survival among HIV-infected persons [4]. PrEP scenarios assumed the scale-up of PrEP in combination with ART and MMC.…”
Section: Interventionsmentioning
confidence: 99%
“…Later studies found that this protective effect against HIV is sustained over extended follow up (up to 6 years in the studies) 6 , 7 . As such, in countries with high HIV prevalence, a generalized heterosexual HIV epidemic, and low rates of male circumcision, WHO and UNAIDS recommend safe, voluntary circumcision for adult men as one important component of a comprehensive strategy to prevent HIV 4 …”
Section: Introductionmentioning
confidence: 99%
“…These results have been sustained among original study participants (Gray et al 2012; Mehta et al 2013) and in non-study community members who opted for VMMC (Auvert et al 2013). Considering the failures of behaviour change for prevention, treatment as prevention, pre- and post-exposure prophylactics, and vaccines, this level of effectiveness has generated great excitement in global HIV programming and donor institutions and propelled the VMMC approach to the forefront of HIV prevention programming.…”
Section: Introducing and Re-introducing Male Circumcisionmentioning
confidence: 77%